SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Biogeography and Anthropogenic Development Shape Mesopredator Distributions in a Rapidly Developing Region - Alex D. Potash; L. Mike Conner; Marcus Lashley; Michael Cherry; Andrew J. Edelman; Elina Garrison; Daniel U. Greene; William Gulsby; Matthew T. Hallett; David S. Jachowski; Paul Taillie; Robert A. McCleery (Journal of Biogeography, 2026)
Aim To investigate effects of anthropogenic development at regional and landscape scales on the distributions of mid‐trophic level mammalian predators (mesopredators) across the southeastern United States. Location The study area encompasses seven ecoregions across a large portion of the southeastern United States. Taxon Mammalian mesopredators. Methods We compiled trail camera data from 21 studies across the southeastern United States and used occupancy modelling to assess mesopredator distributions and account for heterogeneous detection probabilities. We examined drivers of occupancy at regional and landscape scales. At the regional scale, we assessed occupancy patterns across ecoregions differing in topography, productivity, and human population growth. At the landscape scale, we analysed the influence of land cover types (forest, developed, agriculture) and non‐native coyote ( Canis latrans ) activity on occupancy. Results Regionally, mesopredator occurrence was highest in ecoregions characterised by low productivity and greater topographic variability. Common species (predicted occupancy ≥ 0.19) showed positive associations with developed and agricultural land covers, while less common species (predicted occupancy ≤ 0.10) showed negative associations or were too rare to model. Coyote activity had mixed effects, positively associated with some species while negatively associated with others. Main Conclusions Anthropogenic development affects mesopredator communities at both regional and landscape scales, favouring generalist species that are tolerant of human‐modified landscapes.

Quantifying wild pig (Sus scrofa) damage to corn, cotton, and peanut fields using unmanned aerial systems (UAS) in southwestern Georgia, USA. - Justine L. Smith; Roger C. Lowe; L. Mike Conner; Michael T. Mengak (Crop Protection, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Measuring the benefit of a defensive trait: Vigilance and survival probability - William H. Ellsworth; Scott D. Peacor; Richard B. Chandler; L. Mike Conner; Elina P. Garrison; Karl V. Miller; Michael J. Cherry (Ecology, 2024)
Defensive traits are hypothesized to benefit prey by reducing predation risk from a focal predator but come at a cost to the fitness of the prey. Variation in the expression of defensive traits is seen among individuals within the same population, and in the same individual in response to changes in the environment (i.e., phenotypically plastic responses). It is the relative magnitude of the cost and benefit of the defensive trait that underlies the defensive trait expression and its consequences to the community. However, whereas the cost has received much attention in ecological research, the benefit is seldom examined. Even in a defensive trait as extensively studied as vigilance, there are few studies of the purported benefit of the behavior, namely that vigilance enhances survival. We examined whether prey vigilance increased survival and quantified that benefit in a natural system, with white‐tailed deer ( Odocoileus virginianus ) experiencing unmanipulated levels of predation risk from Florida panther ( Puma concolor coryi ). Deer that spent more time vigilant (as measured by head position using camera trap data) had a higher probability of survival. Indeed, an individual deer that was vigilant 75% of the time was more than three times as likely to be killed by panthers over the course of a year than a deer that was vigilant 95% of the time. Our results therefore show that within‐population variation in the expression of a defensive trait has profound consequences for the benefit it confers. Our results provide empirical evidence supporting a long‐held but seldom‐tested hypothesis, that vigilance is a behavior that reduces the probability of predation and quantifies the benefit of this defensive trait. Our work furthers an understanding of the net effects of a trait on prey fitness and predator–prey interactions, within‐population variation in traits, and predation risk effects.

Genetic support for discrete conservation units of the fossorial rodent Geomys pinetis - Sarah I. Duncan; Robert A. McCleery; Celine M. Carneiro; J. T. Pynne; Elizabeth I. Parsons; L. Mike Conner; Steven B. Castleberry; Robert A. Gitzen; James D. Austin (Conservation Genetics, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Prey species increase activity in refugia free of terrestrial predators - Alex D. Potash; L. Mike Conner; Michael Clinchy; Liana Y. Zanette; Robert A. McCleery (Oecologia, 2023)

Season and prey identity mediate the effect of predators on parasites in rodents: a test of the healthy herds hypothesis - Robert L. Richards; L. Mike Conner; Gail Morris; John M. Drake; Vanessa O. Ezenwa (Oecologia, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Prey tells, large herbivores fear the human ‘super predator’ - Daniel A. Crawford; L. Mike Conner; Michael Clinchy; Liana Y. Zanette; Michael J. Cherry (Oecologia, 2022)

Abiotic and biotic factors modulate carrion fate and vertebrate scavenging communities - Kelsey L. Turner; Erin F. Abernethy; L. Mike Conner; Olin E. Rhodes; James C. Beasley (Ecology, 2017)
Carrion is a valuable nutrient resource used by a diversity of vertebrates across the globe. However, vertebrate scavenging ecology remains an understudied area of science, especially in regards to how biotic and abiotic factors influence scavenging community composition. Here we elucidate how fundamental biotic and abiotic factors interact to modulate the efficiency and composition of vertebrate scavengers by investigating scavenging dynamics across a large gradient in carcass sizes and habitat types representative of many temperate ecosystems, as well as between two seasons reflecting differences in invertebrate activity. We found carcass size and season influenced carcass fate and persistence, as well as the richness and composition of vertebrate scavenger communities utilizing carrion resources. Species richness, which increased as carcass size increased and was higher during the cool season, had a significant effect on carcass persistence. In addition, habitat type influenced carcass detection times by vertebrates, and we observed relatively distinct scavenging communities associated with carcasses of differing sizes. This research highlights a pervasive limitation to the interpretation of results of previous studies as research failing to incorporate carcass size and habitat type could result in the over or underrepresentation of vertebrate scavengers in food web dynamics.

Southern toads alter their behavior in response to red-imported fire ants - Andrea K. Long; Daniel D. Knapp; Lauren Mccullough; Lora L. Smith; L. Mike Conner; Robert A. Mccleery (Biological Invasions, 2015)

Effects of prescribed fire, supplemental feeding, and mammalian predator exclusion on hispid cotton rat populations - Gail Morris; Jeffrey A. Hostetler; L. Mike Conner; Madan K. Oli (Oecologia, 2011)

Novel tetranucleotide and pentanucleotide microsatellite loci in the red-cockaded woodpecker (Picoides borealis) - Travis I. Alstad; Brian M. Shamblin; Robert J. Warren; Jonathan M. Stober; L. Mike Conner; Robert J. Cooper; Campbell J. Nairn (Conservation Genetics Resources, 2009)